Borylated N‐Heterocyclic Carbenes: Rearrangement and Chemical Trapping. Issue 10 (23rd January 2019) - Kristinsdóttir, Lilja; Vasko, Petra; Niu, Haoyu; Kolychev, Eugene L.; Campos, Jesús; Fuentes, M. Ángeles; Hicks, Jamie; Thompson, Amber L.; Aldridge, Simon
Abstract: This study details attempts to access N‐heterocyclic carbenes (NHCs) featuring the diazaborolyl group, {(HCNDipp)2 B}, as one or both of the N‐bound substituents, to generate strongly electron‐donating and sterically imposing new carbene ligands. Attempts to isolate N‐heterocyclic carbenes based around imidazolylidene or related heterocycles, are characterized by facile N‐to‐C migration of the boryl substituent. In the cases of imidazolium precursors bearing one N‐bound diazaborolyl group and one methyl substituent, deprotonation leads to the generation of the target carbenes, which can be characterized in situ by NMR measurements, and trapped by reactions with metal fragments and elemental selenium. The half‐lives of the free carbenes at room temperature range from 4–50 h (depending on the pattern of ancillary substituents) with N‐to‐C2 migration of the boryl function being shown to be the predominant rearrangement pathway. Kinetic studies show this to be a first‐order process that occurs with an entropy of activation close to zero. DFT calculations imply that an intramolecular 1, 2‐shift is mechanistically feasible, with calculated activation energies of the order of 90–100 kJ mol −1, reflecting the retention of significant aromatic character in the imidazole ring in the transition state. Trapping of the carbene allows for evaluation of steric and electronic properties through systems of the type LAuCl, LRh(CO)2 Cl, and LSe. A highly unsymmetrical (but nonetheless bulky) steric profile and moderately enhanced σ‐donor capabilities (compared with IMes) are revealed. Abstract : Borylated NHCs : Attempts to access N‐heterocyclic carbenes (NHCs) featuring the diazaborolyl group, {(HCNDipp)2 B}, as the N‐bound substituent(s) are reported. These are characterized by facile N‐to‐C migration, although in the cases of imidazolium systems bearing one diazaborolyl and one Me substituent, the target carbenes can be characterized in situ by NMR measurements, and trapped by reactions with metal fragments and elemental selenium (see figure).